EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN POSITIVE SELF TALK UNTUK MENINGKATKAN AFIKASI DIRI SISWA - Mingtio, Sandi Marahhul; Muhid, Abdul (Universitas Palangka Raya, 2022)
Self-efficacy of students is still one of the problems of students where students who have a very detrimental impact on students, students who have low self-efficacy will indirectly be hampered by the learning process because they will have difficulty in dealing with their daily problems both in learning and problems that arise. he faced. This study aims to determine the effectiveness of group counseling services with positive self-talk to increase students' self-efficacy. The method in this study uses a literature review as a qualitative research. The results prove that the effectiveness of positive self-talk can increase students' self-efficacy. Positive self-talk is proven to be effective in raising students' self-confidence and will indirectly increase student self-efficacy, and students are able to carry out all the tasks, obligations, and problems they face in the school environment.